Efficacy of combination of transcervical Foley catheter and sublingual misoprostol versus sublingual misoprostol for labor induction in pre‐eclampsia at 28–34 weeks. Issue 2 (10th October 2022) - Sharma, Jyotsna; Sagili, Haritha; Keepanasseril, Anish
Abstract: Objective: To compare the efficacy of using a combination of transcervical Foley catheter and sublingual misoprostol with sublingual misoprostol alone for induction of labor (IOL) in women with pre‐eclampsia between 28 and 34 weeks of pregnancy. Methods: This randomized controlled trial was conducted on women with pre‐eclampsia at 28–34 weeks of pregnancy, with unfavorable cervix, admitted to a tertiary hospital in south India. They were randomized to receive either a combination of transcervical Foley catheter and sublingual misoprostol, or sublingual misoprostol alone. Vaginal birth within 24 h of induction, induction to delivery interval, and neonatal morbidity/mortality were the main outcome measures. Results: Vaginal birth within 24 h was higher with the combination of Foley catheter and sublingual misoprostol compared with sublingual misoprostol alone (60% versus 41.4%, P = 0.028). Overall vaginal delivery rates were comparable between the groups (90% versus 80%, P = 0.051). There was no difference in number of doses of misoprostol, and induction to delivery interval between groups. After excluding those with lower likelihood of neonatal survival, live birth rates, mean birth weight, and neonatal intensive care unit admission rates were similar in both groups. Conclusions: Combination of transcervical Foley catheter and sublingual misoprostol was found to be more effective in achieving vaginal birth within 24 h compared with sublingual misoprostol for IOL in pre‐eclampsia between 28 and 34 weeks of pregnancy. Trial Registration Number: CTRI/2018/09/015766; http://ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=27984. Synopsis: Combination of Foley catheter and sublingual misoprostol appears to be more effective than sublingual misoprostol alone for induction of labor in pre‐eclampsia.T